The construction of a 'historical moment': Queen Elizabeth's 2011 visit to Ireland in British and Irish newspapers. (February 2016) - Dekavalla, Marina; Rafter, Kevin
Queen Elizabeth's visit to the Irish Republic in May 2011 was seen by many as a significant moment in the long process of normalisation in Anglo-Irish relations, facilitated by the peace process in Northern Ireland. For journalists, it was a newsworthy story because it captured the values of this process of peace-making in a concrete, organised media event, involving high-profile heads of state, official speeches and photo opportunities. This article examines the representation of this state visit in British and in Irish daily newspapers, and finds similar coverage across a number of shared themes. Journalists in both countries supported the conciliatory message embedded in the media event, with very little questioning, and marginalised voices of opposition. This approach contributed to an ideological consensus that the conflict between the two countries was in the past, with conciliation and collaboration the only future.